Probing the H0 tension with holographic dark energy in unimodular gravity: insights from DESI DR2 - Plaza, Francisco (2025)
Motivated by the recent baryon acoustic oscillation measurements of DESI DR2 collaboration, thisworks presents an extended analysis of a cosmological model based on holographic dark energy withinthe framework of Unimodular Gravity. We probe the model with an extensive set of observations:cosmic chronometers, Pantheon Plus+SH0ES Type Ia supernovae, DESI DR2 BAO distances, quasarX-ray/UV fluxes (two independent calibrations), and Planck 2018 CMB data. The results areanalyzed to assess the model?s ability to alleviate the Hubble tension and, in comparison withthe standard ΛCDM framework, to determine which of the two scenarios is preferred according toBayesian evidence. We conclude that the present implementation of holographic dark energy inUnimodular Gravity, while theoretically appealing, does not alleviate the Hubble tension and isnot statistically preferred by Bayesian criteria when compared with the standard ΛCDM model.Nevertheless, in neither case does the preference become very strong or conclusive against it.